Pesan Dakwah dalam Buku "Tuhan, Maaf Aku Kurang Bersyukur" Karya Malik Al Mughis - Ferina, Lisa; Madya, Efi Brata (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Modern developments offer a variety of media that can be used as a means of conveying da'wah. One of them is the written media or the relevant bil-kalam method used throughout time to present da'wah messages. This research aims to identify the da'wah messages contained in the book "Tuhan, Maaf Aku Kurang Bersyukur" by Malik Al Mughis. This research employs a qualitative methodology, utilizing content analysis techniques. Data was collected through documentation techniques. The findings of this research indicate that in the book Tuhan, Maaf Aku Kurang Bersyukur, there are da'wah messages, namely the aqidah message including faith in Allah in 4 messages, faith in the Book in 2 messages and faith in qada and qadar 2 messages. Moral messages include 11 messages of gratitude and sharia messages include 3 messages of prayer.